Politik Hukum Internasional dalam Transisi Tatanan Dunia Menuju Multipolaritas - Kunkunrat Kunkunrat (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The shift in the world order from a unipolar system to a multipolar system is a global phenomenon that influences the dynamics of international legal politics. The dominance of one major power after the Cold War has begun to shift with the strengthening role of other major powers and the increasing influence of regional actors in global decision-making. This study aims to analyze international legal politics in response to the shift in the global power structure toward multipolarity and its implications for the formation and enforcement of international law. The research method used is normative legal research with a conceptual approach and an international legislative approach, through a literature review of international treaties, legal doctrine, and contemporary international relations practices. The results show that the shift toward a multipolar world order has influenced the process of forming international legal norms, which are increasingly influenced by the political interests of major powers, often weakening global consensus. However, multipolarity also opens up opportunities for creating a more inclusive balance of power and expanding the participation of developing countries in international legal governance. This research is expected to contribute academically to understanding the direction of developments in international legal politics amidst the changing global world order.